Does Quality-of-Life Policing Widen the Net? A Partial Analysis - Golub, Andrew (2004)
In the 1990s, the New York City Police Department instituted a policy of arresting individuals for less serious offenses that impinge on the city’s quality of life (QOL). Critics contend that QOL policing widened the net for arrest, especially among minorities. Alternatively, QOL policing could have created additional opportunities for arresting individuals from the same populations that tend to incur arrests for more serious offenses. This article reports on a comparison of New York City QOL and serious arrestees interviewed in 1999 that provides partial support for this alternative hypothesis; the two groups were similar regarding prior arrests, participation in QOL offenses, and demographic composition. Of note, blacks and Hispanics comprised close to 90% of both arrest populations. These findings suggest that QOL policing does not necessarily widen the net for arrest.